Measurement of stresses in soils of road embankments with the help of Mesdoses - Abdullayev, Seidulla; Izbairova, Aliya; Olga, Kisselyova; Aidos, Toktamyssov; Bondar, Ivan (International Journal of Innovative Research and Scientific Studies, 2025)
The article is a review article devoted to the devices and methods of their use for the experimental study of the stress-strain state of the earth bed of road and railway embankments, approach embankments to bridges, and transport interchanges. Today, an important task in the construction of embankments is the determination of the expected settlement. To measure the stresses in the soil mass of the roadbed, sensors based on strain gauges (Messdozes) are used. The authors consider several types of messdozes according to the ‘classical scheme’, analyze the revealed disadvantages of different designs during laboratory and field tests, and describe the ways of their elimination. The advantages of the modernized scheme of messdozes are described, and the calibration of the modernized sensors (Messdozes) is considered. Modernized sensors have been tested by students of the scientific circle ‘Transport constructions’ under the direction of Associate Professor Bondar I.S. during a series of laboratory experiments carried out on the basis of the testing laboratory ‘Testing of track and artificial constructions’ of ALT University named after Mukhamedjan Tynyshpaev, Almaty.